Comparison of BlockBuster® Laryngeal Mask Airway and Air-Q® Intubating Laryngeal Airway as a conduit for fibreoptic bronchoscopy-guided tracheal intubation in paediatric patients: A randomised comparative study - Kanika Chauhan; Sukhyanti Kerai; Kirti N. Saxena; Lalit Gupta; TH Prathap; Sonia Wadhawan (Indian Journal of Anaesthesia)
Background and Aims: The available supraglottic devices (SGDs) used as conduits for fibreoptic bronchoscope-guided intubation (FOI) in children have shown no difference in terms of time taken for tracheal intubation or success rate on the first attempt. However, several difficulties have been reported during the removal of the SGD after FOI. This study aimed to compare the feasibility of the safe removal of conduits after FOI through BlockBuster® Laryngeal Mask Airway (BlockBuster) and Air-Q® Intubating Laryngeal Airway (Air-Q) in paediatric patients. Methods: This was a randomised comparative study conducted on 66 children between the ages of 1 and 8 years undergoing elective surgeries under general anaesthesia. FOI was performed using BlockBuster or Air-Q as a conduit in study groups. The primary outcome was the time taken and the ease of removing the conduit after FOI. The secondary outcomes included adverse events during conduit removal. We also compared the number of attempts and time taken for the successful placement of these SGDs, as well as for FOI utilising them as conduits. An independent samples t-test was used for normally distributed variables, and a Chi-square test for qualitative variables, with statistical significance set at P < 0.05. Results: The ease of removing the conduit was comparable in both groups (P = 0.21). The mean time taken to remove the conduit was lower in the Blockbuster group [28.03 [standard deviation (SD: 5.90] [95% confidence interval (CI): 26.01, 30.04] seconds] compared to the control group (30.27 (SD: 5.54) (95% CI: 28.38, 32.16) seconds; P = 0.03). There were no adverse events during conduit removal in the BlockBuster and the Air-Q group. The number of attempts (P = 0.317) and time taken for the successful placement of SGDs (P = 0.054) in the study groups and FOI through them was found to be comparable (P = 0.692). Conclusion: For FOB-guided tracheal intubation in paediatric patients, BlockBuster is comparable to Air-Q, and it may be a useful alternative.